2017
DOI: 10.1080/87568225.2017.1366283
|View full text |Cite
|
Sign up to set email alerts
|

Do College Students Use Online Self-Help? A Survey of Intentions and Use of Mental Health Resources

Abstract: Online self-help may help increase the reach of mental health services for college students, but little research has examined students' actual interest/use of these resources. An online survey of 389 college students examined intentions and use of online mental health resources as compared with other support options. Findings indicated the highest intentions/use of informal supports (e.g., parents, friends) for mental health problems and lowest intentions/use for online self-help. However, a subset of students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 26 publications
(19 reference statements)
3
31
0
Order By: Relevance
“…was provided only by two studies and was, respectively, 58.3% 18 and 10%. 23 Sample size was calculated only in one study. 24 All studies included mixed gender with female students making up the largest groups, representing from 52.6% 21,25 to 77.6% 26 of the sample, excluding three studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…was provided only by two studies and was, respectively, 58.3% 18 and 10%. 23 Sample size was calculated only in one study. 24 All studies included mixed gender with female students making up the largest groups, representing from 52.6% 21,25 to 77.6% 26 of the sample, excluding three studies.…”
Section: Resultsmentioning
confidence: 99%
“…18,22,27,31 All other students not using e-mental health reported that they had no need to look for either mental health information or support online. 18,23,32 Mental health-related digital use was associated with the presence of mental health problems in some studies, 18,26,31,37 but not in others 17,24,29 providing mixing results. Findings on the association between gender and emental health use were also unclear: gender differences were little for some authors, 29,38 but strong for others.…”
Section: Students' Mental Health Profiles and Needsmentioning
confidence: 94%
“…Intentions to seek help for a mental health problem were assessed with a modified version of the General Help Seeking Questionnaire (GHSQ), 26 which included items assessing intentions to seek help from a mental health professional as well as various self-help resources. 20 Participants were asked "If you were struggling with a significant personal, emotional, or other mental health problem, how likely is it that you would seek help from the following sources?" Each resource was rated on a 7-point scale from 1 (extremely unlikely) to 7 (extremely likely), with 4 being a neutral score between 3 (unlikely) and 5 (likely).…”
Section: Methodsmentioning
confidence: 99%
“…This is consistent with research in other populations that regularly finds lower intentions to use self-help versus inperson treatment, [16][17][18] as well as a recent study finding similar results with college students. 20 However, self-help is more likely to be viewed as an additional, low intensity treatment option rather than a replacement for in-person therapy so this comparison is not the most relevant in determining whether self-help might improve treatment seeking rates. Rather, the question is whether a notable portion of individuals who are not willing to seek in-person treatment are willing to use self-help, which the current study found.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation